Large‐scale human celebrations increase global light pollution - Francisco Ramírez; Yago Cordón; Diego García; Airam Rodríguez; Marta Coll; Lloyd S. Davis; Andre Chiaradia; Josep L. Carrasco (People and Nature, 2023)
Abstract Culturally dependent human social behaviours involving artificial light usage can potentially affect light pollution patterns and thereby impact the night‐time ecology in populated areas, although to date this has not been examined globally. By analysing continuous (monthly), highly resolved, spatially explicit data on global night lights (Visible and Infrared Imaging Radiometer Suite–Day/Night Band‐VIIRS‐DNB; 2014–2019) with circular statistical techniques, we evaluated whether macro‐cultural activities involving social aggregations and the use of artificial lights shape annual lighting patterns globally. Scheduled routines associated with cultural‐specific festivities appear to be important drivers of observed seasonal patterns in urban night‐time lights. For instance, the display of Christmas lights between Christmas and Epiphany Day celebrations (December–January) coincides with the annual peak in urban night‐time light intensity in Christian countries. Analogously, night celebrations during the Holy Month of Ramadam (from May to July) or the month‐long period of Karthika Masam (from October to November) fits with annual night light peaks in Muslim and Hindu countries. Annual peaks of urban light intensity in China and Vietnam also match with Chinese and Vietnamese (Tê't) New Year celebrations (January–February). In contrast, predominantly Buddhist countries, which do not have such prominent and prolonged celebrations involving artificial lights, show a relatively uniform distribution of night light peaks throughout the annual cycle. Social behaviour and sociocultural contexts help explain how people modify the global nightscape and contribute to light pollution globally. Understanding the cultural contexts responsible for peaks in artificial light usage is an important first step if humans are to mitigate any deleterious effects associated with global increases in night‐time light pollution. Read the free Plain Language Summary for this article on the Journal blog.